R.G. Collingwood, Analytical Philosophy And Logical Positivism - James Connelly (Baltic International Yearbook of Cognition, Logic and Communication, 2008)
R.G. Collingwood is not normally associated with analytic philosophy, neither negatively nor positively. He neither regarded himself, nor was regarded by his contemporaries and their successors, as an analytical philosopher. However, the story is more interestingly complex than this, both because Collingwood is one of the few pre-analytics in the UK who continues to be of interest to current analytical philosophers, especially in relation to the philosophy of art and history and his conception of metaphysics, and because he mounted a critique of analytical philosophy in the years of its emergence.
Keywords: philosophy; analytic philosophy; history of philosophy